Association Between Medication Adherence and Admission Blood Pressure Among Patients With Ischemic Stroke. Issue 2 (March 2019) - Chen, Min-Jie; Wu, Chan-Chan; Wan, Li-Hong; Zou, Guan-Yang; Neidlinger, Susan Holli
Abstract : Background: Poor medication adherence is one of the most important factors underlying uncontrolled blood pressure, and ensuing hypertension is the leading risk factor for stroke. However, the influence of prestroke medication nonadherence on the admission blood pressure of patients with hypertension who have had an ischemic stroke remains unclear. Objective: The aims of this study were to explore the influence of medication nonadherence on the admission blood pressure of patients with hypertension who have had an ischemic stroke and to analyze the reasons for medication nonadherence preceding stroke. Methods: A sample population of 301 patients with hypertension who have had an ischemic stroke was recruited. A questionnaire was used to investigate sociodemographic data and reasons for nonadherence. The 4-item Medication Adherence Scale was used to investigate prestroke medication adherence. Blood pressure was measured upon patient admission. Logistic regression analysis was used to identify factors influencing adherence. Results: In this cohort, 80.73% of the patients exhibited uncontrolled blood pressure on admission, and 26.58% had undiagnosed hypertension. Of the patients aware of their diagnosis, 75.11% were nonadherent and 10.40% had never used antihypertensive medicines. Uncontrolled admission blood pressure was positively influenced by medication nonadherence. The main causes of nonadherence included forgetfulness (58.08%), lack of belief in the need for long-term antihypertensive treatment (27.27%), and no awareness of the importance of long-term medication (24.75%). Conclusions: Stroke education in China should focus on patients' poor understanding of the importance for sustained antihypertensive medication adherence to improve blood pressure control and prevent stroke.